Nature-Based Tourism and Mental Health: A Study of “Green Therapy” for Tourists in Bali - Wirawan, Putu Eka; Yani, Ni Wayan Mega Sari Apri (Politeknik Negeri Bali, 2025)
This study investigates the relationship between nature-based tourism and tourists’ mental health through the concept of green therapy in Bali, a destination renowned for its diverse natural landscapes and wellness traditions. Green therapy is conceptualized as a psychological restoration process derived from direct interaction with natural environments, where elements such as vegetation, forest ambience, flowing water, and natural sounds contribute to stress reduction, emotional regulation, and improved cognitive clarity. Using a qualitative design, data were collected from fifteen tourists through in-depth interviews and focus group discussions, and analysed using thematic analysis to identify core experiential patterns. The findings indicate that engagement with Bali’s natural settings including forest walks, terraced rice fields, meditation, and yoga, significantly enhances emotional well-being, reduces anxiety, and strengthens self-awareness. However, the restorative potential of these experiences is diminished by overtourism and overcrowding in popular destinations. These results underscore the need for sustainable and decentralized destination management that preserves ecological quality while maintaining therapeutic value. The study further suggests integrating green therapy principles into tourism planning to enhance visitor well-being and support long-term sustainable development. Overall, the research contributes empirical insight into how Bali’s natural assets can function as an effective medium for psychological healing.